2005
DOI: 10.25336/p6q889
|View full text |Cite
|
Sign up to set email alerts
|

Living Arrangements among Single Mothers in India

Abstract: Abstract:A large proportion of two parent households transition into single parent households upon marital disruption. Single parent households, especially female headed households face an increase in the risk of poverty. This study focuses on whether widow status in India influences the likelihood of household headship in India. This study is based on the most recent National Family Health Survey 1998-1999, in India. The population of interest includes all mothers aged 15 to 49 years, without a spouse, living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…First, not all one-parents choose to co-reside with their extended families. For example, in the case of India, Swain and Pillai (2005) found that age, number of children, and nature of marital dissolution often determine living arrangements among single mothers. In addition, household heads who are not immediate parents may face uncertainty in returns from education that may affect their decisions about resource allocation for goods with private returns (Townsend, 1994).…”
Section: Theoretical Motivationmentioning
confidence: 97%
“…First, not all one-parents choose to co-reside with their extended families. For example, in the case of India, Swain and Pillai (2005) found that age, number of children, and nature of marital dissolution often determine living arrangements among single mothers. In addition, household heads who are not immediate parents may face uncertainty in returns from education that may affect their decisions about resource allocation for goods with private returns (Townsend, 1994).…”
Section: Theoretical Motivationmentioning
confidence: 97%
“…Many studies were conducted among single parents regarding their psychological, social, and emotional aspects and well-being (Walker & Hennig, 1997;Hetherington, 2003;Weitoft, Hjern, Haglund & Rosén, 2003;Bradshaw, Keung, Chzhen, Nieuwenhuis, & Maldonado, 2018;Rani, 2006;Pujar, Chanda & Hittalamani, 2018;Chavan, 2018;Swain & Pillai, 2005;Mishra, Thamminaina & Mishra, 2021;Daniel, 2021) but there is an urgent need for extending these concerns to the children who live with a single parent because the factors that they are struggling with have a potential to lead them to many adverse life circumstances and psychological consequences.…”
Section: Psychological Well-being (Pwb)mentioning
confidence: 99%
“…[ 15 ] Single mothers are viewed as insufficient; consequently, they become socially excluded and are subjected to extreme prejudice and condemnation. [ 16 17 ] In general, they have a lower level of education, a poorer household income, and are more likely to reside in extreme poverty, experience unemployment, and cultivate depression than married working mothers. [ 18 ] Whereas rural single parents perceived themselves to be deprived in relational, socioemotional, material, and other dimensions.…”
Section: Introductionmentioning
confidence: 99%